La Créolité, vingt ans après - Jean Bernabé (Anglophonia)
About twenty years after the publication of the essay In Praise of Creoleness, it was necessary to come back to the concept that constitutes its main theme, even if it meant revisiting, or even revising, in a self-critical perspective, some of its ideological and political implications. Beyond the semantic value of the word "creole" and analysis of the modes and processes of linguistic creolization, this article aims at containing the various potential risks, among which, for instance, that of communitarianism which may follow from an unduly essentialist sense of the term, the sharing of ancestors then appearing as both the optimal definition of Creoleness and the antidote to the communitarian reduction.